Strabismus in Bronzino’s paintings: a hallmark of a realistic painter? - Lazzeri, Davide; Cianchini, Giuseppe; Nicoli, Fabio; Casini, Giamberto; Lazzeri, Stefano (Acta Biomedica Atenei Parmensis, 2019)
The present article analyses eleven paintings of Bronzino, one of the major painters of the late Italian Mannerism, in which the sitters are portrayed with deviating eyes. The reasons why Bronzino may have included a truant eye in his subjects are herein discussed. We consider the ‘wandering’ eye as a hallmark of Bronzino’s style. The inclusion of strabismus may be part of the Mannerism tendency of using exaggerated hallmarks but pursuing at the same time an increasing realism that was typical of the 15th and 16th century movements.